The effects of customer orientation and entrepreneurial orientation on SMEs performance: the mediating role of innovation capabilities. The methodological moderators’ comparative study - Aklilu Tukela Bekata; Chalchissa Amentie Kero (Journal of Innovation and Entrepreneurship)
Abstract The main objective of this study is to investigate the significance of customer and entrepreneurial orientation for SMEs’ innovation capabilities and performance. This study used an explanatory research design and multi-stage sampling to gather primary data from Hawassa city in Ethiopia. The study applied structural equation modeling (SEM) to analyze the empirical data of 321 SMEs operating in the study area to verify the hypotheses of the proposed structural regression model. According to the SEM results, customer orientation and entrepreneurial orientation have a direct and beneficial impact on the performance of SMEs. This effect is more distinct for multi-item measures. Moreover, innovation capabilities partially mediate the relationships between customer orientation and entrepreneurial orientation and the performance of SMEs. The study makes a significant theoretical and practical contribution to the application of dynamic capabilities and resource-based theories in the context of SMEs. The findings contribute to the literature by demonstrating the significance of strategic insights in enhancing innovation capabilities and the performance of SMEs. By incorporating methodological moderators and comparing SMEs in different sectors and economic contexts, the study broadens its applicability and relevance. The findings provide empirical generalizations and highlight areas of inconsistency in the strategic orientation–performance casual effects.